2023
DOI: 10.1038/s41467-023-37089-5
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic impacts on threatened species erode functional diversity in chelonians and crocodilians

Abstract: The Anthropocene is tightly associated with a drastic loss of species worldwide and the disappearance of their key ecosystem functions. The orders Testudines (turtles and tortoises) and Crocodilia (crocodiles, alligators, and gharials) contain numerous threatened, long-lived species for which the functional diversity and potential erosion by anthropogenic impacts remains unknown. Here, we examine 259 (69%) of the existing 375 species of Testudines and Crocodilia, quantifying their life history strategies (i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…We also estimated other life history traits from these IPMs, but we decided to focus our analyses on generation time and net reproductive output only, as they describe the principal axes of the life history variation in our species (Figs. S8-S9), as well as in other reptiles (Rodriguez-Caro et al . 2023).…”
Section: Methodsmentioning
confidence: 93%
“…We also estimated other life history traits from these IPMs, but we decided to focus our analyses on generation time and net reproductive output only, as they describe the principal axes of the life history variation in our species (Figs. S8-S9), as well as in other reptiles (Rodriguez-Caro et al . 2023).…”
Section: Methodsmentioning
confidence: 93%
“…However, while there is theoretical and empirical support for a community-level slow-fast trait response, conflicting observations challenge this hypothesis. First, while the slow-fast spectrum is well defined in plants, additional axes of variation in functional and life-history strategies (e.g., reproductive strategies, and their defining traits such as the timing of reproductive onset and reproductive allocation) have been identified in both plants and other organisms 29 , 30 , and these may respond to different drivers and dominate the distribution of certain organismal groups, decoupling them from the response of others 3 , 31 . Furthermore, guilds might vary in their strength of response to the drivers of the slow-fast functional axis 32 and could respond over different spatiotemporal scales 33 leading to weak overall coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Many threatened species are functionally unique, with uncommon trait combinations (Carmona et al., 2021; Matthews et al., 2022), and some studies have demonstrated that the most endangered species tend to be large and long‐lived, with few offspring and small geographic ranges (e.g., Carmona et al., 2021). At a global scale, it has been detected that the extinction of endangered species of different taxonomic groups would cause functional diversity loss (e.g., Ali et al., 2023; Carmona et al., 2021; Rodríguez‐Caro et al., 2023; Toussaint et al., 2021) and a constraint of the functional space, i.e., the theoretical space whose dimensions are traits or functional strategies in which each species occupies a position based on its characteristics (Rodríguez‐Caro et al., 2023). At smaller scales, the extinction of such species causes a loss of functional diversity leading to more functionally homogeneous communities (e.g., Soares, Palmeirim, et al., 2022; Villéger et al., 2014).…”
Section: Introductionmentioning
confidence: 99%